2015
DOI: 10.1007/s00442-015-3466-4
|View full text |Cite
|
Sign up to set email alerts
|

Adult survival selection in relation to multilocus heterozygosity and body size in a tropical bird species, the Zenaida dove, Zenaida aurita

Abstract: Both phenotypic and genetic quality can influence the survival of individuals through time, although their relative influences are rarely addressed simultaneously. Here we used capture-mark-recapture modelling to assess the influence of both multilocus heterozygosity (MLH) and body size on apparent adult survival in a tropical bird species, the Zenaida dove, Zenaida aurita, using a sample of 391 individuals genotyped at 11 microsatellites, while controlling for the effects of sex. No effect of body size on eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 83 publications
1
8
1
Order By: Relevance
“…In addition to body mass, heterozygosity also positively influenced the survival of female Black Grouse. This is similar to the findings of many other studies where genome-wide heterozygosity and heterozygosity at specific loci have been associated with increased survival in some vertebrate species [mammals (Banks et al 2010;Forcada and Hoffman 2014); fish (Evans et al 2010); birds (Worley et al 2010;Cézilly et al 2016)]. Similar to body size, the relationship between survival and heterozygosity has been mainly found in juveniles (e.g.…”
Section: Discussion Heterozygosity and Fitnesssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to body mass, heterozygosity also positively influenced the survival of female Black Grouse. This is similar to the findings of many other studies where genome-wide heterozygosity and heterozygosity at specific loci have been associated with increased survival in some vertebrate species [mammals (Banks et al 2010;Forcada and Hoffman 2014); fish (Evans et al 2010); birds (Worley et al 2010;Cézilly et al 2016)]. Similar to body size, the relationship between survival and heterozygosity has been mainly found in juveniles (e.g.…”
Section: Discussion Heterozygosity and Fitnesssupporting
confidence: 90%
“…Similar to body size, the relationship between survival and heterozygosity has been mainly found in juveniles (e.g. Bean et al 2004;AcevedoWhitehouse et al 2006;Cohas et al 2009), but there is growing evidence that these effects continue throughout adulthood (Velando et al 2015;Cézilly et al 2016). We do not have data directly linking individual chick mortality and heterozygosity, but it is likely to be significant because of the strong relationship between inbreeding depression and chick mass (Soulsbury et al 2011), which in itself is a major determinant of chick survival (Ludwig et al 2010).…”
Section: Discussion Heterozygosity and Fitnessmentioning
confidence: 99%
“…Genetic theories of sexual selection predict that most ornamental secondary sexual traits provide reliable indication of the genetic quality of their bearers (Brown , Fromhage et al ). Although direct relationships between coloration and genome‐wide heterozygosity or level of inbreeding have been evidenced in birds (García‐Navas et al , Bolund et al , Ferrer et al ) and neutral locus heterozygosity is known to influence adult survival in our species (Cézilly et al ), we found only moderate evidence for a relationship between plumage coloration and individual heterozygosity in the Zenaida dove. However, ornaments could be linked to other aspects of genetic quality such as MHC diversity (von Schantz et al , Grahn , Dunn et al , Whittingham et al ).…”
Section: Discussioncontrasting
confidence: 78%
“…Variation in inbreeding, and thus individual heterozygosity, is of particular interest for its relevance to questions related to kin selection, dispersal and conservation, among many others. In the last decade, molecular ecologists have strived to examine inbreeding in natural populations through the use of heterozygosity–fitness correlations (HFCs), utilizing multiple genetic markers to obtain heterozygosity estimates for individuals, and then correlating these metrics to traits of interest such as survival (e.g., Cézilly, Quinard, Motreuil, & Pradel, ) or reproduction (e.g., Townsend & Jamieson, ; Velando, Barros, & Moran, ). Recent analyses utilizing neutral markers, especially microsatellites (e.g., Velando et al., ) or genomewide SNPs (e.g., Huisman, Kruuk, Ellis, Clutton‐Brock, & Pemberton, ), have detected HFCs in a variety of contexts, although a systematic review of HFCs across 61 species found that relationships tend to be weak, albeit with wide variation in reported effect sizes (Chapman, Nakagawa, Coltman, Slate, & Sheldon, ).…”
Section: Introductionmentioning
confidence: 99%
“…C ezilly, Quinard, Motreuil, & Pradel, 2015) or reproduction (e.g., Townsend & Jamieson, 2013;Velando, Barros, & Moran, 2015).…”
mentioning
confidence: 99%